THE NEED FOR BREAKTHROUGH AND INTEGRATED POLICY INNOVATION IN INCREASING ORIGINAL REGIONAL INCOME - Din, Badariah Haji; Wahyudhi, Indra (CENTRAL ASIA AND THE CAUCASUS, 2021)
The pace of decentralization in Indonesia after independence and reformation era has resulted in debates that have not ended. The ebb and flow of support for decentralization has sometimes led to conflicts of opinion, up to the adaptation and synchronization of laws, regulations and policies. In the spirit and era of change, the local government has a heavy burden to finance its routine agenda. Meanwhile, taxes and levies are not sufficient for operations due to slow competitiveness and adaptation of policy innovations. Bekasi regency is in a great knot and faces tough challenges because it is in a large industrial area. However, this is because the existing regulation means that local governments do not have much flexibility in regulating and managing their original sources of income. So that this research through a qualitative approach which is operationalized by structured interviews is able to present data that even policy actors find constraints and have many ideas on how to increase their own local income. And finally it can be concluded from the historical aspect up to now, the problem of the relationship between the regional center in mainly supporting the increase in local revenue has always found political contestation and is framed through regulations.